Upaya Guru Pendidikan Agama Islam Dalam Pembinaan Akhalakul Karimah Siswa Kelas VII SMP Negeri 2 Mojogedang Tahun Pelajaran 2014/2015 - MUSTOFA, Ari Imam, Drs. Bambang Raharjo, M. Ag, Drs. Saifuddin Zuhri, M. Ag (2015)
The role of education in life is very important to establish civilization and the human personality. With education, people can understand environment in the face it so that he can make a great work and beneficial to society and the nation. Therefore Islam placing education at the very high position and ordered so that his people always bejalar lifelong. Efforts to establish the student to become a man who is faithful and devoted God Almighty and has akhlakul karimah, it is necessary their religious education. Implementation of Islamic education is implementation of the National Education Act. The goal is to plan in prepare students to understand and practice the teachings Islam can be achieved in accordance with what is expected. The problems that can be adopted in this study is A the efforts of teachers in coaching moral PAI students in Junior High School 2 Mojogedang. The purpose of this study is to describe the form of effort PAI teachers do in the moral formation of students in Junior High School 2 Mojogedang. This research method using qualitative methods of writing. Technical collecting data used in this study, by using interview, observation and documentation. While the analysis of the data in This study used a qualitative descriptive technique. Based on the research results and data analysis has been done, it can be concluded that from theory the function and role of teachers PAI, From the research and study of theory, it can be PAI concluded that the effort in coaching Guru Guru morals that PAI as tutors or giving guidance to teachers Telling students to Doing Duha prayer to the mosque, asking the students to perform prayers Dluhur to the mosque in congregation and Familiarize students if met teacher, friend or anyone else in the school environment greetings, act and utter a polite and kind to teachers, staff and fellow students. Teachers PAI for example or role model with PAI teacher always punctual in teaching, discipline and mutual respect. Teachers PAI as a motivator is to PAI teacher gives the story that the success obtained sister level other not in because they were always disciplined in learning, so people are disciplined the study will be successful in the future. PAI teacher of some efforts in fostering the morals of students, teachers PAI can leverage development efforts morals facilitate teachers in achieving the learning objectives so as to achieve the competence of teachers and destination learning well.